Electrophoretic deposition of carbon nanotubes on aluminium for capacitor application. (2nd January 2022) - Schneider, M.; Weiser, M.; Krasmann, C.; Seidel, N.; Malcher, P.; Reinfried, M.
ABSTRACT: Multiwalled carbon nanotubes (MWCNT) were electrophoretically deposited from an environmentally friendly aqueous solution on aluminium current collectors which were carbon coated by physical vapour deposition. The carbon coating proved to be stable under electrophoretic deposition (EPD) conditions up to EPD voltage of U = 50 V and avoided any undesirable oxidation of the aluminium during the deposition process. The kinetics of the deposition was described and could be easily controlled by the suspension concentration and the deposition time. The deposition rate at U = 50 V is about 0.03 mg cm −2 min −1 . As anodic oxide formation could be prevented the electrical contact to the current collector was improved allowing the surface area to be increased by MWCNT to be used as a double-layer capacitor. The gravimetric capacitance obtained was about 8 F g −1 .